ПОНЯТТЯ «КОМУНІКАТИВНА КОМПЕТЕНТНІСТЬ» У СУЧАСНОМУ МУЗИЧНО-ПЕДАГОГІЧНОМУ ДИСКУРСІ - Фан, Сє (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті на основі теоретичного аналізу наукових підходів щодо інтерпретації ключових понять роботи «компетентність» та «комунікація», «комунікативна компетентність», компонентної структури останнього, невизначеність його сутності з позиції музичної педагогіки запропоновано власне тлумачення змісту «комунікативна компетентність» як здатність особистості ефективно застосовувати знання і вміння в міжособистісних відносинах, які засновані на взаємодії суб’єктів у соціальному, культурному, естетичному, емоційно-ціннісному та професійному контекстах. В статье на основе теоретического анализа научных подходов к интерпретации ключевых понятий работы «компетентность» и «коммуникация», «коммуникативная компетентность», компонентной структуры последнего, неопределенность его сущности с позиции музыкальной педагогики предложено собственное толкование содержания «коммуникативная компетентность» как способность личности эффективно применять знания и умения в межличностных отношениях, основанных на взаимодействии субъектов в социальном, культурном, эстетическом, эмоционально-ценностном и профессиональном контекстах. In the article, on the basis of theoretical analysis of scientific approaches concerning the interpretation of key concepts of «competence» and «communication», «communicative competence», component structure of the latter, the uncertainty of its essence from the position of musical pedagogy, was offered their own interpretation of the meaning «communicative competence» as the ability of the individual to effectively apply knowledge and skills in interpersonal relationships that are based on the interaction of social, cultural, aesthetic, emotional, evaluative and professional contexts. By general communication categories we mean: verbal and communicative, informative and theoretical, creative and organizational, technological, innovative and research related categories. It is proved that communicative competence in the professional activity of a pianist is the main instrument for implementing his/her creative ideas, control his/her own performing actions; it is an inner personal communication tool between ideas and social needs of today.